The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/nph.17555
|View full text |Cite
|
Sign up to set email alerts
|

RNAi suppression of DNA methylation affects the drought stress response and genome integrity in transgenic poplar

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 116 publications
(178 reference statements)
1
36
0
Order By: Relevance
“…Early studies have already shown that chromosomal damage, such as breaks in DNA, DNA methylation, and abnormal gene expression, may accumulate during the process of seed aging, causing the frequency of affected cell damage to surpass a threshold after which seeds lose their germinability [58]. Moreover, although epigenetic modifications can be reset between generations, the transmission of gradually acquired epimutations over generations appears to be higher in plants than in animals [62][63][64][65]. Epigenetic alterations, especially those involving DNA methylation, may contribute to transgenerational epigenetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have already shown that chromosomal damage, such as breaks in DNA, DNA methylation, and abnormal gene expression, may accumulate during the process of seed aging, causing the frequency of affected cell damage to surpass a threshold after which seeds lose their germinability [58]. Moreover, although epigenetic modifications can be reset between generations, the transmission of gradually acquired epimutations over generations appears to be higher in plants than in animals [62][63][64][65]. Epigenetic alterations, especially those involving DNA methylation, may contribute to transgenerational epigenetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, knockdown of miR393 promoted growth and biomass production in poplar, which was verified in STTM393 transgenic poplar lines [ 88 ]. RNAi suppression of DNA methylation affected the drought stress response and genome integrity in transgenic poplar [ 89 ]. Additionally, expression of artificial microRNAs (amiRNAs) in plants using virus- and non-virus-based expression vectors achieved RNAi effects on specific transcripts [ 90 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Nonetheless, its role in plant stress tolerance was recently proposed. The DDM1-deficient line in poplar trees was shown to have improved drought tolerance accompanied by DNA methylation and transcriptional alterations [15].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent publication provides evidence for the role of DDM1 in the response of plants to environmental conditions. RNAi-DDM1 lines of poplar (Populus tremula × Populus alba) were more tolerant to drought-induced cavitation and presented thousands of differentially methylated regions along with transposable elements activation [15]. We aimed to assess the possible involvement of DDM1 in heat stress response in tomato.…”
Section: Introductionmentioning
confidence: 99%